Peran Pemahaman Karakteristik Siswa Cerdas Istimewa Berbakat Istimewa (Cibi) dalam Merencanakan Proses Belajar yang Efektif dan Sesuai Kebutuhan Siswa - Wulan, Dwi Kencana (Bina Nusantara University, 2011)
This study focused on the importance of the process to understand the characteristics of Gifted and talented students (CIBI) with special needs, in planning and implementing effective learning process that will be able to facilitate the development of student’s ability optimally. The reseach samples are teachers of acceleration class in one of government senior high school (X) in Bekasi West Java. Data collection was done through the method of Focus Group Discussion (FGD) and interviews. The data indicate, in general, teachers have learned hat gifted and talented students have different characteristics in thinking skills than other students have in general. However, this has not been followed by the planning and delivering an appropriate learning process that met the gifted students’ needs. It appears that an accelerated program for gifted students only facilitates the development of cognitive aspect and accelerates the delivery of appropriate curriculum materials provided, while the socio-emotional aspects of students have given less attention.